Rancang Bangun Aplikasi Mobile EduPlay sebagai Media Pembelajaran dan Penilaian Otomatis Mahasiswa Magang - Wan Hasib Al Aslamy; Rindu Puspita Wibawa (Universitas Negeri Surabaya, 2026)
Abstract— The internship program at PT. Avolut Global Indonesia faces challenges such as unstructured material delivery, a manual assessment system, and the absence of a real-time monitoring mechanism. This study designed and developed the EduPlay mobile application as a learning medium and automated assessment for interns. The application was developed using the Rapid Application Development (RAD) method with the stages of Requirements Planning, User Design, Construction, and Cutover. The technology stack used included React Native (Expo) for the mobile interface, PostgreSQL as the database, and Supabase as the backend-as-a-service. Testing was conducted using Black Box Testing with 10 functional scenarios. All scenarios resulted in a Success status, including user authentication, material grouping (UI/UX, Programming, Data Analyst), interactive quizzes, and automatic score calculation using the formula Score = (B/N) x 100. EduPlay has been proven to improve the effectiveness of internship program evaluation through consistent, transparent, and structured assessments.Keywords— Mobile Application, EduPlay, Rapid Application Development, Black Box Testing, Automated Assessment, Internship, React Native, Supabase.